PHOTOGRAPHIC STUDY OF ECLIPSING BINARIES BW CAS AND AT MON - Antoniuk, K. A. (Одеські астрономічні публікації, 2017)
Photometric elements for BWCas and AT Mon, brightness of the comparison stars and moments of 15 weakenings are determined. The period of BW Cas is twice than that previously published by Diethelm (1997).